2022
DOI: 10.1177/1356336x221086366
|View full text |Cite
|
Sign up to set email alerts
|

The curriculum took a back seat to huff and puff: Teaching high school health and physical education during Covid-19

Abstract: This study examined secondary (high) school teachers’ experiences of online delivery of health and physical education (HPE) during Covid-19 suppression measures in one Australian state in 2020. Research has noted the use of blended learning and flipped classrooms in HPE, yet little is known about the delivery of fully online school HPE. Semi-structured interviews occurred with eight high school HPE specialist teachers, providing qualitative data for analysis. The analysis of teachers’ experiences indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
1
23
0
4
Order By: Relevance
“…Castañeda-Babarro et al [26] reported that individuals experienced increases in sedentary time along with decreases in PA during the pandemic, in contrast to our findings. Several recent studies have also established that social distancing due to COVID-19 has reduced PA levels [13,15,16], thus leading to various adverse effects [14,16,27].…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Castañeda-Babarro et al [26] reported that individuals experienced increases in sedentary time along with decreases in PA during the pandemic, in contrast to our findings. Several recent studies have also established that social distancing due to COVID-19 has reduced PA levels [13,15,16], thus leading to various adverse effects [14,16,27].…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…Studies have reported a decrease in general PA due to the COVID-19 pandemic [13][14][15][16]. Woods et al [16] appropriately emphasized that such decreases in PA due to social distancing can lower resistance to viral infection and increase the risk of damage to the immune, respiratory, cardiovascular, musculoskeletal, and nervous systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classroom teachers often consider PE a release from "high status" subject work rather than an integral aspect of students' education (Lynch & Soukup, 2017;Milić et al 2022). This can result in HPE receiving less emphasis, time, and resourcing than other KLAs (Cruickshank et al, 2021b;Birch & Auld, 2020;Lowry et al, 2022) which can be problematic in light of Australian teachers stating a lack of time is a key barrier to achieving HPE outcomes (Morgan & Hansen, 2008;Peralta et al, 2021;Williams, 2017). In addition, the Measurement Framework for Schooling in Australia, 2020 (ACARA 2020) identifies literacy, numeracy, civics and citizenship, ICT literacy, and science literacy as key performance measures within the National Assessment Program, thus highlighting marginalisation and a subsequent lack of accountability for reporting on the HPE learning area.…”
Section: Hpe Pe and He In Australian Primary Schoolsmentioning
confidence: 99%
“…The authors are sure that such a catastrophic decline in the indicators of healthy children is directly related to the lack of sports in children's lives. Moreover, to change the situation, it is necessary, at least, to pay special attention to physical education lessons at school [20,21]. One of the basic physical qualities that need to be developed throughout life is general endurance.…”
Section: Introductionmentioning
confidence: 99%